Activated prothrombin complex concentrate in patients receiving emicizumab prophylaxis: from evidence to clinical practice - Robert F. Sidonio, Jr.; Guy Young; Carmen Escuriola Ettingshausen; Johnny Mahlangu; Margareth C. Ozelo; Alok Srivastava; Jerzy Windyga; Hye–Youn Lee; Aurelia Lelli; Steven W. Pipe (Research and Practice in Thrombosis and Haemostasis)
Nonfactor therapies (NFTs) such as emicizumab are increasingly becoming established for bleed prophylaxis in people with hemophilia A. Both classes of bypassing agents (BPAs; activated prothrombin complex concentrate [aPCC] and recombinant activated factor [F]VII [rFVIIa]) are required for effective bleed management in people with inhibitors receiving NFT prophylaxis, owing to the variable hemostatic responses to aPCC and rFVIIa seen in different patients. Early reports of rare thrombotic events in clinical trials of emicizumab led to the development of guidelines preferring the use of rFVIIa over aPCC for the management of breakthrough bleeding and major surgery in patients receiving emicizumab. Since these guidelines were issued, data from clinical and real-world studies have emerged that support the efficacy and safety of aPCC in this setting. In this narrative review, we aimed to evaluate the evidence on bleed management with aPCC in people with hemophilia A with inhibitors receiving emicizumab prophylaxis, as well as other NFTs. These emerging data indicate that aPCC used at doses of ≤ 100 U/kg/day in people with inhibitors receiving emicizumab is not associated with thrombotic microangiopathy or thrombotic events. As more NFTs become available for bleed prophylaxis, both classes of BPAs will be needed for bleed management in people with inhibitors. Thus, optimal use of BPAs is critical and will require an understanding of the factors that influence BPA selection, such as bleed type and location, clinical response, dosing and duration of use, accessibility and availability, and patient or caregiver preference.